IIdentification, characterization, and evolutionary features of Brevipalpus-transmitted viruses causing citrus leprosis disease - Jesus, Camila Chabí de (2020)
Citrus leprosis (CL) is a non-systemic disease affecting citrus orchards mainly in Latin America. Vectored by mites of the genus Brevipalpus, the disease is caused by a heterogeneous group of viruses of the genera Cilevirus (family Kitaviridae) and Dichorhavirus (Family Rhabdoviridae), which are collectively known as Brevipalpus-transmitted viruses (BTVs). Originally described in Florida, USA, at the end of the 19th century, CL was detected in the 1930s in Brazil, Argentina, and Paraguay and, more recently, in several countries in Latin America. Citrus leprosis is caused mainly by the cilevirus citrus leprosis virus C (CiLV-C) and, in less extension, by BTVs whose molecular diversity has been poorly understood. The current study aimed to deeply describe the CiLV-C population and to characterize three new dichorhaviruses causing CL. To address the CiLV-C variability, we examined a cohort of 425 symptomatic samples collected over Latin America in the period 1932-2019, including eight herborized samples conserved for more than 80 years. Diversity and phylogenetic evaluation indicated that the CiLV-C population is subdivided into three lineages, named CRD, SJP, and ASU, whose members show signs of inter-clade recombination processes. Members of the clade CRD were identified widespread in the subcontinent in samples collected as early as 1932, while those of the clade SJP were restricted to commercial orchards in the citrus belt of São Paulo-Minas Gerais, in samples collected after 2015. The lineage ASU is represented by a single isolate collected in Asunción, Paraguay, in 1937, and the diversity and distribution of current members, if any, are still unknown. The most recent common ancestor of viruses of the three lineages likely originated in contact with native vegetation in a wild ecosystem of South America before the citrus introduction in America. Current subpopulations of CiLV-C are genetically well-differentiated, show a very low genetic diversity where almost every haplotype is unique, and, as a whole, are under purifying selection. Three new species of dichorhaviruses were identified in samples of sweet oranges (Citrus sinensis) collected in non-commercial or small orchards of distant and climatically distinct regions in Brazil. While citrus leprosis virus N (CiLV-N) and citrus bright spot virus (CiBSV) were detected in the Southern and Southeastern regions, citrus chlorotic spot virus (CiCSV) was found in the Northeast of the country. Besides sweet oranges, CiCSV naturally infects plants of the species Talipariti tiliaceum, and Agave desmettiana. CiLV-N is transmitted by mites of the species Brevipalpus phoenicis s.s., which also likely vector CiBSV. In contrast, CiCSV is transmitted by B. yothersi, the most abundant Brevipalpus spp. in citrus orchards in Brazil, and the primary vector of CiLV-C, whereas B. aff. yothersi mites, probably a new species, might also transmit it. In addition to disclosing the structure and the evolutionary forces driving the population of CiLV- C, this work reveals new CL-causing BTVs. Altogether, it exposes a fragment of the challenging scenario for the development of the citrus industry facing the latent risk of crop saturation by the prevalent viruses and the threat of the putative emergent ones.